Amyotrophic lateral sclerosis in pregnancy is associated with a vascular endothelial growth factor promoter genotype. (28th January 2014) - Lunetta, C.; Sansone, V. A.; Penco, S.; Mosca, L.; Tarlarini, C.; Avemaria, F.; Maestri, E.; Melazzini, M. G.; Meola, G.; Corbo, M.
<x xml:space="preserve">Abstract</x> Background and purpose The occurrence of amyotrophic lateral sclerosis (ALS) during pregnancy is uncommon and the effect of one on the other is not well described. Methods The clinical and genetic features of five cases of ALS are reported with an onset during pregnancy or within 1 month from delivery. Charts from 239 women with a diagnosis of ALS attending the neuromuscular clinics at the Neuromuscular Omnicentre (NEMO) and at IRCCS Policlinico San Donato from 2008 to 2011 were reviewed. Results Of these, 12.8% of the women in child‐bearing age had a diagnosis of ALS during pregnancy or immediately after delivery. Genetic screening of the major causative genes revealed two mutations in superoxide dismutase 1 (SOD1) gene; the analysis of vascular endothelial growth factor (VEGF) promoter variation showed a segregation of the haplotype CA/AG (−2578C/A; −1190A/G) in patients developing ALS related to pregnancy. No effects on foetal development or neonatal course were observed. Conclusions Pregnancy may unmask ALS but whether this is coincidental is unclear. Hormonal and inflammatory modifications might trigger ALS in subjects with increased susceptibility to oxidative stress related to the toxic function of SOD1 or in subjects with a reduction of neuroprotective molecules such as VEGF.